From Beliefs to Practices: Understanding English Teachers’ Literacy Perspectives in the Indonesian Context - Yulia Agustina; M. Adib Nazri; Laila Wati (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2026)
This study investigated English teachers' beliefs and practices related to literacy teaching in the context of Indonesian education. The primary aim was to understand how teachers' conceptions of literacy are reflected in their classroom teaching practices, as well as to identify factors that influence the alignment or misalignment between beliefs and implementation. This study employed a convergent parallel mixed methods design involving 52 respondents who were recruited simultaneously in August–September 2025 through a Google Form. Quantitative data were analysed using Spearman's rho correlation test, while qualitative data were analysed thematically. The correlation test results showed that the four dimensions (linguistic, cognitive, social, and development) of teacher literacy were positively and significantly interrelated, with the highest correlation between the cognitive and developmental dimensions (r = 0.706), indicating that strong conceptual understanding greatly contributes to classroom practice. Qualitatively, teachers have integrated reading, writing, and speaking, but face the main challenges of low student reading interest and limited basic vocabulary. It is concluded that teacher literacy was a complex construct, where teachers' beliefs are often hampered by contextual constraints in the field. The implications of this study emphasize the need for institutional support and professional training to increase student motivation and provide relevant learning resources.